ANALYSIS OF A HYBRID AC-DC MEDIUM VOLTAGE BENCHMARK NETWORK WITH RENEWABLE PRODUCTION USING QUASI-STATIC TIME SERIES - Diaconu, Teodor-Ioan; Sănduleac, Mihai (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2025)
Benchmark networks, known also as test networks developed by renowned international organizations need to be upgraded in order to keep pace with current and future trends regarding grid development. This paper presents a hybrid AC-DC MV benchmark network in order to study its behavior and advantages in various situations. A novel method for dynamic analysis of the grid is presented and demonstrated using the proposed hybrid network by implying Quasi-Static Time Series (QSTS), with time series short enough not to require complex modelling of what is happening between two time steps.